Climate, environment and society in southern Italy during the last 2000 years. A review of the environmental, historical and archaeological evidence. (15th March 2016) - Sadori, Laura; Giraudi, Carlo; Masi, Alessia; Magny, Michel; Ortu, Elena; Zanchetta, Giovanni; Izdebski, Adam
Abstract: This paper examines the interrelationship between the natural and human history of Sicily over the last 2000 years. It presents a close comparison of the data from the key multi-proxy site of Lago di Pergusa – located inland in the eastern part of Sicily – with the existing archaeological and textual evidence on the socio-economic processes. The article also includes a review of the available natural proxy archives from the Central Mediterranean. On the basis of the isotope and pollen data from the Lago di Pergusa core PRG2, we identified two humid periods (ca. 450–750 AD and ca. 1400–1800 AD) as well as a dry one (ca. 1100–1350 AD); our evidence corresponds closely with other environmental palaeoclimate proxies from the Mediterranean region. In our synthesis of the environmental, historical and archaeological evidence from southern Italy, we argue that during both periods of increased humidity – that is during the late antique-Byzantine times and during the late medieval and early modern periods – intense agricultural use of the Sicilian landscape developed on an unprecedented scale. This in turn contributed to the impressive demographic and economic expansion visible during these periods. A sudden period of aridity followed the first of these eras of humidity-related agricultural growth. This climatic shift, dated to around 750 AD, corresponds to a decrease in synanthropic taxa and a recovery of arboreal vegetation. We argue that in this case a climatic change contributed to socio-economic decline. Moreover, as this change occurred prior to the Arab invasion of Sicily in AD 827, the environmental processes may help to explain the collapse of Byzantine society on Sicily which, in turn made the Muslim conquest possible. After this event, there occurred a longer period of agricultural decline, lasting until around 1000 AD, after which we see the first signs of a slow recovery. Ongoing research in nearby archaeological sites will help defining if it was a local change or a regional, potentially climate-induced phenomenon. Although textual evidence records considerable population losses during the later Middle Ages as a result of the Black Death, the effects of the plague are not obviously apparent in the pollen data, except for some short term fluctuations. Highlights: In the last 2000 years we found evidences of humid and dry periods. Periods of increased humidity coincided with agricultural and demographic expansions. A drying trend could have contributed to the collapse of Byzantine society and Arab conquest. There is a match between the Arabic conquest and a decline in agriculture. The impact of the Black Death is not clearly visible in the pollen data.